PENGARUH INFRASTRUKTUR JALAN DAN LISTRIK TERHADAP INVESTASI DAN PERTUMBUHAN EKONOMI DI PROVINSI BALI - Mahyoga, Putu Dhika; Sri Budhi, Made Kembar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.10.TAHUN.2022DO - 10.24843/EEB.2022.v11.i10.p01, 2022)
Infrastructure is the driving force of the economy so that it will attract investors and can increase economic growth. This study aims to analyze 1) the influence of road and electricity infrastructure on investment in Bali Province, 2) the influence of road and electricity infrastructure on economic growth in Bali Province, and 3) the influence of road and electricity infrastructure on economic growth in Bali Province through investment. This study uses secondary data obtained from the Bali Provincial BPS and literature related to research in the 2016-2020 time period. Data was collected using non-participant observation methods and then the data were analyzed using path analysis. The test results show that road infrastructure has no significant effect on investment in Bali Province, while the electricity variable has a positive and significant effect on investment in Bali Province. Road infrastructure, electricity, and investment have a positive effect on economic growth in Bali Province. Investment is not a variable that indirectly mediates the influence of road and electricity infrastructure on economic growth in Bali Province.